2019
DOI: 10.1103/physreve.99.032118
|View full text |Cite
|
Sign up to set email alerts
|

Dirac wave transmission in Lévy-disordered systems

Abstract: We investigate the propagation of electronic waves described by the Dirac equation subject to a Lévy-type disorder distribution. Our numerical calculations, based on the transfer matrix method, in a system with a distribution of potential barriers show that it presents a phase transition from anomalous to standard to anomalous localization as the incidence energy increases. In contrast, electronic waves described by the Schrödinger equation do not present such transitions. Moreover, we obtain the phase diagram… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 60 publications
1
9
0
Order By: Relevance
“…However, strong long-range correlations are known to induce a localization-delocalization transition [39,40,41,42,43,44,45,46], thus leading to the emergence of the reported transmission band. Notice that the average logarithmic transmission is not an appropriate quantity to clearly signal this delocalization transition, in agreement with the similar delocalization phenomenon reported in graphene superlattices with Levy-distributed barrier spacements [50].…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…However, strong long-range correlations are known to induce a localization-delocalization transition [39,40,41,42,43,44,45,46], thus leading to the emergence of the reported transmission band. Notice that the average logarithmic transmission is not an appropriate quantity to clearly signal this delocalization transition, in agreement with the similar delocalization phenomenon reported in graphene superlattices with Levy-distributed barrier spacements [50].…”
Section: Resultssupporting
confidence: 84%
“…On the other hand, transmission still results reminiscent of Klein tunneling at small incidence angles. Recently, it was shown that these two regimes leads to either standard or anomalous scaling of the transmission when the barrier widths are distributed following a scale-free Levy distributions [50]. Further, fractal [51], self-affine potentials [52] and long-range scale-free correlations in the barrier heights and widths [53] as well in the velocity profile [54] were also considered.…”
Section: Introductionmentioning
confidence: 99%
“…Email address: nguyenbaphi@muce.edu.vn https//doi.org / 10.25073/2588-1124/vnumap.4498 During the recent few decades, the influence of spatially correlated disorder on the wave propagation and localization properties has been attracted much attention from theoretical as well as experimental researchers [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. It has been demonstrated that some special kinds of short-range correlated disorder can produce delocalized eigenstates even in one dimension [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…During the recent few decades, the influence of spatial disorder correlations on the localization properties has been studied extensively [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]. It has been demonstrated both theoretically and experimentally that some special types of short-range correlated disorder can produce extended eigenstates even in one dimension [10,11,26].…”
Section: Introductionmentioning
confidence: 99%